Sociology of sport - Giulianotti, Richard , 1966- (Sage library of tourism, hospitality and leisure, 2011)
With no other reference work like this in the field, this seminal collection focuses on this large subdiscipline within the fields of sociology and sport studies. It includes both classic and contemporary papers drawn from a range of subjects across the social sciences